CITIZEN MOVE TO JOURNALIST? DINAMIKA PRAKTIK JURNALISME WARGA MELALUI MEDIA BARU - Yuniar, Anada Dwitha (Jurnal Nomosleca, 2018)
Abstract The rise of new media and ubiquitos of technology encourages the practice of news reporting by citizens. Public space crisis in mainstream media, making new media elucidate to revitalize the opportunities that citizens be apart of social changes. The new media has provided the widest space for citizens to engage in the delivery of news or information. This involvement is also supported by the development of citizen media or which is an extension of mainstreamÂ  media such as Kompasiana owned by Kompas and NET CJ owned by Netmediatama. However, the trend of citizen journalism is still a question of whether to lead to the manifestation of democracy or even cause new problems related to journalism credo? This research is a qualitative research using descriptive analysis and using constructivist paradigm. Data collection using documentation study of citizen journalism practices that exist on NET CJ and Kompasiana website. This study also uses literature review with similar research to strengthen arguments and analysis. Keywords: new media, citizen journalism, citizen media, public participatoryDOI :https://doi.org/10.26905/nomosleca.v4i2.2545